Embroidery on the Cover and Beyond: Intermedial References of Threaded Embellishments on the Brazilian Editorial Scene - Erika Viviane Costa Vieira (Interfaces)
This paper approaches paratextual elements employing embroidery or stitching as illustrations. These elements used in Brazilian editorial projects reflect the ethos of an ambivalent type of feminine poetic imagery in which the materiality of fabric and thread conveys affects. Stitches become intermedial references, to borrow from Irina Rajewsky’s (2005) semiotic categories, enacting what Liliane Louvel (2011) calls parapictorial and interpictorial practices. Further frameworks that inform the present article are the studies on textiles by Anni Albers (1974) and Rozsika Parker (1984). The argument that embroidered illustrations may mobilize material and sensorial media modalities also draws from Lars Elleström (2021) and relies on the notion of paratext defined by Gérard Genette (1997). The over-arching purpose is to reflect upon the intermedial role of embroidery and sewing on the Brazilian editorial scene, with the goal of encouraging discussions on materiality and the interplay between affect, femininity, image, text, and touch.